2D Organic Materials for Optoelectronic Applications. Issue 2 (12th October 2017) - Yang, Fangxu; Cheng, Shanshan; Zhang, Xiaotao; Ren, Xiaochen; Li, Rongjin; Dong, Huanli; Hu, Wenping
Abstract: The remarkable merits of 2D materials with atomically thin structures and optoelectronic attributes have inspired great interest in integrating 2D materials into electronics and optoelectronics. Moreover, as an emerging field in the 2D‐materials family, assembly of organic nanostructures into 2D forms offers the advantages of molecular diversity, intrinsic flexibility, ease of processing, light weight, and so on, providing an exciting prospect for optoelectronic applications. Herein, the applications of organic 2D materials for optoelectronic devices are a main focus. Material examples include 2D, organic, crystalline, small molecules, polymers, self‐assembly monolayers, and covalent organic frameworks. The protocols for 2D‐organic‐crystal‐fabrication and ‐patterning techniques are briefly discussed, then applications in optoelectronic devices are introduced in detail. Overall, an introduction to what is known and suggestions for the potential of many exciting developments are presented. Abstract : Assembling organic nanostructures into 2D form offers the advantages of molecular diversity, flexibility, and unique physical properties, providing exciting future prospects for optoelectronic applications. The applications of organic 2D materials for optoelectronic devices are reviewed. After a brief discussion on the protocols for 2D crystal fabrication and patterning techniques, their applications in optoelectronic devices are introduced and an outlook is provided.